An analysis of premature cracking associated with microstructural alterations in an AISI 52100 failed wind turbine bearing using X-ray tomography. (5th March 2017) - Gould, Benjamin; Greco, Aaron; Stadler, Kenred; Xiao, Xianghui
Abstract: Crack surrounded by local areas of microstructural alteration deemed "White etching cracks" (WECs) lead to unpredictable and premature failures within a multitude of applications including wind turbine gearbox bearings. While the exact cause of these failures remains unknown, a large number of hypotheses exist as to how and why these cracks form. The aim of the current work is to elucidate some of these hypotheses by mapping WEC networks within failed wind turbine bearings using high energy X-ray tomography, in an attempt to determine the location of WEC initiation, and the role of defects within the steel, such as inclusions or carbide clusters. Four completely subsurface WECs were found throughout the presented analysis, thereby confirming subsurface initiation as method of WEC formation. Additionally, a multitude of small butterfly like cracks were found around inclusions in the steel, however further analysis is needed to verify if these inclusions are initiation sites for WECs. Graphical abstract: Highlights: Crack networks were mapped using X-Ray Tomography in order to study crack morphology and inclusion interaction Subsurface crack initiation was verified as the dominant method of premature failure formation within wind turbine bearings Serial sectioning and etching were used to observe the presence of microstructural alterations surrounding all cracking Instances of small cracking around inclusions were observed, and are likely the initiation points for larger crack networks. The detected failures likely occurred due to an accelerated fatigue process as opposed to classical rolling contact fatigue.